A new approach: Predicting height of a person from joint ratio of fingers - Güllü, Merve; Ceyhan, Eyüp Burak; Ulucan, Ceren; Ceyhan, Eyüp Burak (Association for Computing Machinery acmhelp@acm.org, 2016)
This paper presents the existence of relation among the heights of Turkish citizens and joints of fingers. It also investigates the ratios of index fingers and ring fingers. Obtained features such as index fingers and ring fingers taken from right and left hands, heights, genders and age info of 49 male individuals between 18- 79 years old, 45 female individuals between 18-55 years old, and total 94 individuals were used for this investigation. A system was also developed for predicting heights from 2D:4D rate of index fingers and ring fingers automatically for the first time. The system has a number of models trained with four algorithms. The results have shown that the proposed system can achieve the task with the highest accuracy having 73.40%. © 2017 Elsevier B.V., All rights reserved.
5th International Conference on Network, Communication and Computing, ICNCC 2016 -- Kyoto -- 127265
Keywords: 2d:4d; Biometrics; Digital Forensic; Finger Length; Height; Model; Prediction